AGE-FRIENDLY PACKAGING DESIGN: FEATURES AND CHALLENGES - LI, JUN; DUBRIVNA , A. (Art and Design, 2024)
The purpose: to analyze and explore the application and development of age-friendly design in the packaging sector to address the challenges presented by aging. Provide assistance for the advancement and progression of future age-friendly packaging design, aiming to support relevant research and practical endeavors to drive forward. Methodology. The methodology includes general scientific principles of systematization, comparison and generalization of the investigated problem, which made it possible to define and scientifically substantiate existing theories, conceptual approaches to understanding the features of packaging design. The use of the analytical method led to the establishment of conceptual foundations for the scientific perspectives of understanding the methods and practices of integrating of age-friendly approach into packaging design. The results. A systematic review of the relevant theories of age-friendly packaging design was conducted, exploring the application methods and practices of age-friendly design principles in packaging design. The integration of academic research findings provided a comprehensive reference for practical implementation. Scientific novelty. The integration of age-friendly design principles into packaging design, proposing solutions for aging-related challenges, is innovative and of practical significance, Bringing a human-centric perspective and intelligent methodologies to future packaging design. Practical meaning. In response to the societal challenge of population aging, the initiative aims to draw attention within the packaging design industry to issues related to aging, fostering improvement and innovation in relevant products and services. Ultimately, this endeavor seeks to enhance the quality of life for the elderly population.